PENGARUH KONSENTRASI INISIATOR 2-HIDROKSI-2-METIL-FENILPROPANON TERHADAP SIFAT KONDUKTIVITAS DAN KARAKTERISTIK KOMPOSIT POLIMER KOLESTERIL AKRILAT-ITO - Ahmad Zaini Assidiqih; Afrizal Afrizal; Arif Rahman (Jurnal Riset Sains dan Kimia Terapan, 2017)
This study aims for shyntesized of composite of cholesteryl acrylate polymer-indium tin oxide (PCA-ITO) and the characteristic, and also its conductivity properties. Synthesized of PCA-ITO Composite by using UV Curing method with initiator 2-Hydroxy-2-Methyl PhenylPropanone (Darocur 1173). This research using vary of concentration initiator darcor were 0; 0,125; 0,250; 0,375; 0,500; 0,625 % V/V. The FTIR characterization results show a shift of wave numbers between the PCA-ITO composite FTIR spectrum and its pure cholesteryl arcylate (KA) FTIR spectrum. Based on the XRD diffraction pattern thereis a high intensity peak a 2Î¸=30Â° which is the typical peak of ITO and there is a peak at 2Î¸=7Â° which is the peak of the cholesteryl acrylate-ITO. The greater the initiator concentration the ITO and PCA begin to mix and look at the morphology of the surface with englarged. The LCR Meter data show that the conductivity value of the PCA-ITO composite without the initiator is smaller when compared with the addition of the initiator. Keywords. Cholesteryl acrylate, Indium Tin Oxide, Initiator darocure 1173, Photopolymerization, Conductivity